Time Course and Clinical Relevance of Neurological Deterioration After Endovascular Recanalization Therapy for Anterior Circulation Large Vessel Occlusion Stroke - Li, Zibao; Zhang, Hongchuan; Han, Jian; Chu, Zhaohu; Zhao, Shoucai; Yang, Qian; Huang, Xianjun; Zhou, Zhiming (Frontiers in Aging Neuroscience, 2021)
Neurological deterioration (ND) is a devastating complication for patients with ischemic stroke after endovascular recanalization therapy (EVT). We aimed to investigate the time course and clinical relevance of ND after EVT. Consecutive patients with acute ischemic stroke who underwent EVT for large arterial occlusions of the anterior cerebral circulation were enrolled between May 2015 and December 2019. The National Institutes of Health Stroke Scale (NIHSS) scores were assessed before EVT, at the end of EVT, at 24 h (d1), on day 3 (d3), on day 15 (d15), at discharge and anytime when ND was indicated. ND was defined as an increase of ≥ 4 points in the NIHSS score and was divided into acute ND (AD, within 24 h), subacute ND (SD, d1 to d3), and delayed ND (DD, d3 to d15 or discharge). Using multivariable logistic regression analysis, we explored predictors and outcomes of ND at different time periods. As a result, of 343 patients, 129 (37.6%) experienced ND, including 90 (26.2%) with AD, 27 (7.9%) with SD and 12 (3.5%) with DD. Multivariable logistic regression analysis revealed that history of hypertension, cardioembolic stroke, lower Alberta Stroke Program Early Computed Tomography Score (ASPECTS), and poor collaterals were significantly associated with an increased risk of AD; history of hypertension, lower ASPECTS, poor collaterals, and unsuccessful recanalization, with SD; and high admission NIHSS score, with DD. In addition, patients who experienced AD (OR = 10.22, P < 0.001), SD (OR = 15.89, P = 0.004) or DD (OR = 8.31, P = 0.015) were more likely to have poor outcomes. ND was a strong predictor of poor stroke outcomes. Management of related risk factors at different ND time periods might improve the prognosis of EVT.